2020
DOI: 10.1055/s-0040-1701219
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Sinonasal Mucosal Melanoma in Patients Treated with Systemic Immunotherapy

Abstract: Objectives Surgical resection is widely accepted as a critical component for definitive treatment of sinonasal mucosal melanoma. Systemic immunotherapy, including multiple newer agents, has been used to treat metastatic or unresectable disease. In this study, we examine its efficacy in locoregional control when used in conjunction with surgical resection for primary mucosal lesions. Design Present study is a retrospective review of all patients at a tertiary academic medical center with primary sinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The treatment of choice is ablative surgery with free resection margins. However, the complex anatomy of the sinonasal cavities near some vital structures makes it impossible to obtain tumor-free resection margins, with important aesthetic and functional sequelae, unjustified by a distant metastasis rate of more than 40% [12][13][14][15] . The approach used may be endoscopic, external, or combined, depending on the extent of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of choice is ablative surgery with free resection margins. However, the complex anatomy of the sinonasal cavities near some vital structures makes it impossible to obtain tumor-free resection margins, with important aesthetic and functional sequelae, unjustified by a distant metastasis rate of more than 40% [12][13][14][15] . The approach used may be endoscopic, external, or combined, depending on the extent of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation dose information and technique are inconsistent in the current literature. In contrast, stereotactic radiotherapy (1,200 cGy in 2 fractions) is recommended for adrenal metastasis 15 . Systemic therapy does not bring the desired effects in survival 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other studies suggest that immunotherapy may confer an OS benefit, but only for patients with metastatic disease. In a retrospective study of four sinonasal mucosal melanoma patients with distant metastases treated with primary surgery and immunotherapy, Chao and colleagues reported that immunotherapy may improve clinical outcomes for patients with metastatic disease, but concluded that surgery remains the best upfront treatment 34 . Additionally, a recent analysis of the NCDB by Ganti et al found that immunotherapy use was associated with improved OS in patients with metastatic sinonasal mucosal melanoma 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of four sinonasal mucosal melanoma patients with distant metastases treated with primary surgery and immunotherapy, Chao and colleagues reported that immunotherapy may improve clinical outcomes for patients with metastatic disease, but concluded that surgery remains the best upfront treatment. 34 Additionally, a recent analysis of the NCDB by Ganti et al found that immunotherapy use was associated with improved OS in patients with metastatic sinonasal mucosal melanoma. 17 Similarly, a multicenter retrospective study of 229 metastatic mucosal melanoma patients observed that those receiving immunotherapy had significantly improved OS compared to those receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%